2013
DOI: 10.1017/s1460396913000149
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapist perspectives on cone-beam computed tomography practices and response to information

Abstract: Introduction: With recent technological advances in image-guided radiation therapy (IGRT), through conebeam computed tomography (CBCT), more image-related clinical information is being collected, at more frequent intervals throughout the treatment course. As radiation therapy (RT) programmes further develop IGRT technology, the aim of this study is to assess whether the distribution and communication of professional responsibilities is evolving to ensure appropriate use of the technology.Methods: Radiation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Volumetric image guidance has greatly impacted the roles and responsibilities of the radiation therapist [3,5]. It has also been previously identified that with an increasing scope of practice driven by technological advances, there is inconsistency in perceptions, practices, and role assignment when interpreting CBCT images [4]. As such, continuing professional development activities, such as the CBCT module presented in this study, is a step toward providing appropriate information through an appropriate medium at the right time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Volumetric image guidance has greatly impacted the roles and responsibilities of the radiation therapist [3,5]. It has also been previously identified that with an increasing scope of practice driven by technological advances, there is inconsistency in perceptions, practices, and role assignment when interpreting CBCT images [4]. As such, continuing professional development activities, such as the CBCT module presented in this study, is a step toward providing appropriate information through an appropriate medium at the right time.…”
Section: Discussionmentioning
confidence: 88%
“…In the changing environment of volumetric IGRT technology, skill development and integration of knowledge is essential to ensure clinical competence of radiation therapists [4]. At the onset of clinical implementation of CBCT technology at our institution, to ensure therapists were readily equipped to manage daily decision-making regarding patient setups, a two-level training program was designed and implemented [5].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of standardizing guidelines in an image guidance era include ensuring the safety and effectiveness of IGRT [12]. As online IGRT increases volumetric information at the front line, radiation therapists are increasingly involved in image analysis and decision making that affects the accuracy and precision of patient treatment [8,11,12]. Dissemination of standardized documentation facilitates clinical implementation, ensures consistency in clinical practice, and aids in the education and professional development of radiation therapists [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) guidance systems allow for online volumetric visualization of patient anatomy, enabling daily setup variations to be quantified and corrected prior to treatment delivery, while monitoring daily patient changes and deformations [5,6]. Efficient incorporation of daily CBCT application and decision making into the clinical workflow is influenced by the confidence in image assessment by end users, and their experience and comfort with volumetric image visualization and literacy [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation